Positive mental health literacy: development and validation of a measure among Norwegian adolescents - Hanne Nissen Bjørnsen; Mary˗Elizabeth Bradley Eilertsen; Regine Ringdal; Geir Arild Espnes; Unni Karin Moksnes (BMC, 2017)
Abstract Background Mental health literacy (MHL), or the knowledge and abilities necessary to benefit mental health, is a significant determinant of mental health and has the potential to benefit both individual and public mental health. MHL and its measures have traditionally focused on knowledge and beliefs about mental -ill-health rather than on mental health. No measures of MHL addressing knowledge of good or positive mental health have been identified. Aim: This study aimed to develop and validate an instrument measuring adolescents' knowledge of how to obtain and maintain good mental health and to evaluate the psychometric properties of the instrument. More specifically, the factor structure, internal and construct validity, and test-retest reliability were assessed. Methods The participants were Norwegian upper secondary school students aged 15-21 years. The development and validation of the instrument entailed three phases: 1) item generation based on the basic psychological needs theory (BPNT), focus group interviews, and a narrative literature review, 2) a pilot study (n = 479), and 3) test-retest (n = 149), known-groups validity (n = 44), and scale construction, item reduction through principal component analysis (PCA), and confirmatory factor analysis (CFA) for factor structure and psychometric properties assessment (n = 1888). Results Thirty-two items were initially generated, and 15 were selected for the pilot study. PCA identified cross-loadings, and a one-factor solution was examined. After removing five problematic items, CFA yielded a satisfactory fit for a 10-item one-factor model, referred to as the mental health-promoting knowledge (MHPK-10) measure. The test-retest evaluation supported the stability of the measure. McDonald's omega was 0.84, and known-groups validity test indicated good construct validity. Conclusion A valid and reliable one-dimensional instrument measuring knowledge of factors promoting good mental health among adolescents was developed. The instrument has the potential to complement current measures of MHL and may be useful when planning mental health promotion activities and evaluating public mental health education initiatives in adolescents.